Influence of prey abundance and abiotic factors on the long-term home-range and movement dynamics of spotted grunter Pomadasys commersonnii in an intermittently open estuary. Issue 2 (19th August 2016) - Maree, BA; Cowley, PD; Næsje, TF; Childs, A-R; Terörde, AI; Thorstad, EB
Abstract : Long-term home-range and movement dynamics of spotted grunter Pomadasys commersonnii and the distribution of their dominant prey, the sandprawn Callichirus kraussi, were investigated in the intermittently open East Kleinemonde Estuary, South Africa. In addition, the effects of fish length, diel cycle, season and other abiotic factors on home range and area use were examined. Nine adult spotted grunter (326–489 mm total length) were tagged with acoustic transmitters, and their movements were studied by manual tracking on six consecutive days and nights during each of five tracking sessions from March to November 2004. In addition, movement patterns were recorded by stationary data-logging receivers. Kernel home ranges (95% utilised distribution) varied in size (mean: 76 797 m 2  , range: 26 296–165 321 m 2 ), but were all located in the lower one-third of the 3.6 km-long estuary. There was no effect of season, the diel cycle or fish length on the home-range estimates. However, the distribution of prey corresponded with the home-range distribution of tagged fish. Although sandprawn distribution was highly variable within and among transects and depth classes, sandprawns were most abundant in the lower region of the estuary, which corresponded to the home-range distribution of spotted grunter. Spatial distribution of prey appears to be a dominant factor influencing home-range parameters of this species within an intermittently open estuary.